Economic feasibility of solar irrigation pump in India: An insight from Andhra Pradesh - R, RENJINI V; JHA, GIRISH K; SINHA, J P (The Indian Journal of Agricultural Sciences, 2021)
This paper attempts to examine the potential and utilisation of solar power with a special focus on solar powered irrigation system in India. The solar capacity has mostly concentrated in Southern and Western states but most of the states have not attained their solar power potential. Installation of the solar irrigation pump with state and central financial support is impressive in states like Rajasthan, Chhattisgarh and Andhra Pradesh. Further, the life cycle cost of solar photovoltaic (SPV) water pump and diesel pump was calculated based on the field survey data collected during 2019 from three districts of Andhra Pradesh. The capital cost of SPV pump per horsepower is 8 times higher than that of diesel pump but operation and maintenance cost of solar found to be significantly lower than that of diesel pump which is making solar powered irrigation system economically viable.